Professional practice model for a hospital network: Nursing methodology research - Torres - Acosta, Doris Helena; Pulido – Barragán, Sandra Patricia; Archila – Hernández, Edwin Darío; Laverde – Contreras, Olga Lucía; Sánchez - Herrera, Beatriz (Revista Cuidarte, 2025)
Highlights • Changes in service delivery structures require nursing to follow common guidelines to achieve its purposes. • Professional nursing practice models are important guides for making caring visible and focused. • The development of models for teaching hospital networks requires the involvement of both care practice and teaching. • The developed professional practice model strengthens leadership and compassionate and safe nursing care. Introduction: The emergence of hospital networks requires nursing models to guide practice and research. Objective: To develop a professional practice model to guide nursing care practice, teaching, and research in a teaching hospital network. Materials and Methods: This study involved Nursing Methodology Research conducted within an academic-service partnership over three years in a hospital network in Colombia. It followed a humanistic theoretical framework and a collective construction technique with guideline-based development and analysis. It included four consecutive phases: 1) Identification of the need for the model within the Hospital Network, 2) recognition of nursing metaparadigm concepts for practice, 3) formulation and prioritization of the assumptions required to achieve nursing mission and vision, and 4) consolidation, sharing, and validation of the model. A total of 156 out of the 185 nurses in the organization participated. Results: The model developed for the Hospital Network consists of three essential components: compassion, safe care, and nursing leadership. Discussion: The collective participation of the nursing staff and the work made within the academic-service partnership facilitated the adoption of the model. This development responds to the Hospital Network’s strategic guidelines for quality of care, includes internal and external validation, and adheres to international standards. Conclusion: The "Leadership in Compassionate and Safe Care" nursing practice model guides, facilitates, and makes visible teaching and care practice and nursing research inside and outside of the Hospital Network. How to cite this article: Torres-Acosta Doris Helena, Pulido-Barragán Sandra Patricia, Archila-Hernández Edwin Darío, Laverde-Contreras Olga Lucía, Sánchez-Herrera Beatriz. Professional practice model for a hospital network: Nursing methodology research. Revista Cuidarte. 2025;16(1):e4348. https://doi.org/10.15649/cuidarte.4348